Solid-state battery with enhanced solid electrolyte
Patent Information
- Application Number
- JP2026503560
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-05-20
- Filing Date
- 2024-09-10
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 【0009】 本発明の様々な目的、特徴、特性及び利点は、そのすべてが本明細書の一部を形成する添付図面及び添付の特許請求の範囲と併せて、実施形態の以下の説明から明らかになり、より容易に理解される。添付図面では、同様の参照数字は、様々な図中の対応する又は類似の部分を指定するために利用され得、描写される様々な要素は、必ずしも縮尺通りではない。
Smart Images

Figure 2026533938000001_ABST
Abstract
Description
Technical Field
[0001] Cross-Reference to Related Applications
[0001] This application claims priority and the benefit of U.S. Provisional Patent Application No. 63 / 539,990, filed on September 22, 2023, entitled "Solid-State Battery with Enhanced Solid Electrolyte", the entire contents of which are incorporated herein by reference.
[0002] Statement Regarding Government Interests
[0002] This invention was made with government support under DE-AC05-76RL01830 awarded by the U.S. Department of Energy to Battelle Memorial Institute Pacific Northwest Division operating Pacific Northwest National Laboratory (PNNL). The Government has certain rights in this invention pursuant to Research & Development Services Agreement 81614 between the assignee of the present application and Battelle Memorial Institute Pacific Northwest Division.
Background Art
[0003]
[0003] Lithium-ion batteries are commonly used to power electronic devices. A standard lithium-ion battery contains a liquid electrolyte. These liquid electrolytes are conventionally composed of flammable liquid organic compounds. In the event of overcharging or short circuit, for example, conventional lithium-ion batteries with liquid electrolytes may pose safety and fire hazards.
Summary of Invention
Problems to be Solved by the Invention
[0004]
[0004] Solid-state lithium-ion batteries can potentially provide improvements over conventional liquid electrolyte lithium-ion batteries, for example, better safety, thermal stability, energy density, power density, and / or a wider operating temperature range relative to conventional lithium-ion batteries. However, several challenges remain in the development of effective and widely adoptable solid-state lithium-ion batteries. In particular, there is a continuing need for solid electrolytes that can function effectively when used within solid-state lithium-ion batteries.
Means for Solving the Problems
[0005]
[0005] Disclosed herein are compounds: Na x Li 3-x YCl6 (wherein x is greater than 0 and less than 3, for example, x is greater than 0.5 and less than 2.5) Examples include Na2LiYCl6, NaLi2YCl6, Na 0.5 Li 2.5 YCl6, Na 1.5 Li 1.5 YCl6 and Na 2.5 Li 0.5 YCl6. The disclosed compounds can be used as effective solid-state battery electrolytes. The disclosed compounds are
Formula
[0006]
[0006] Also disclosed herein is a solid electrolyte comprising the compound Na x Li 3-x YCl6 (0<x<3). When used in a solid electrolyte, the disclosed compounds may have a trigonal crystal structure. Disclosed herein are compounds Na xLi 3-x It is also a solid-state battery including a solid electrolyte containing YCl₆ (0<x<3). The solid electrolyte can advantageously function to conduct lithium ions and sodium ions. Accordingly, the solid-state battery may be configured as a lithium-ion battery, a sodium-ion battery, or a dual-ion battery.
[0007]
[0007] Disclosed herein is also a method of manufacturing a solid-state battery such as a solid-state lithium-ion battery or a solid-state sodium-ion battery. The method includes disposing a positive electrode in a container, disposing a negative electrode in the container, and disposing a solid electrolyte between and in conductive contact with the positive electrode and the negative electrode within the container, wherein the solid electrolyte comprises Na x Li 3-x YCl₆ (0<x<3). Na x Li 3-x The YCl₆ (0<x<3) compound optionally includes a trigonal crystal structure.
[0008]
[0008] This summary is provided to introduce in a simplified form specific concepts that are further described below in the Detailed Description. This summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used as an indication of the scope of the claimed subject matter.
[0009]
[0009] Various objects, features, characteristics and advantages of the present invention will become apparent and more readily understood from the following description of the embodiments, taken in conjunction with the accompanying drawings and the appended claims, all of which form a part of this specification. In the accompanying drawings, like reference numerals may be used to designate corresponding or similar parts throughout the various figures, and the various elements depicted are not necessarily to scale. [[ID=24】Brief Description of the Drawings
[0010] [Figure 1A] [[ID=30】
[0010] is a schematic diagram of an exemplary solid-state lithium-ion battery during discharge. [Figure IB]
[0011] This is a schematic diagram of an exemplary solid-state lithium-ion battery during charging. [Figure 2A]
[0012] This is a schematic diagram of an exemplary solid sodium-ion battery during discharge. [Figure 2B]
[0013] This is a schematic diagram of an exemplary solid sodium-ion battery during charging. [Figure 3]
[0014] The results of powder X-ray diffraction (XRD) for various tested NaxLi3-xYCl6 samples are shown. [Figure 4]
[0015] The atomic percentages of Na, Li, Y, and Cl from XPS analysis are shown. [Figure 5]
[0016] This shows the ionic conductivity of various tested NaxLi3-xYCl6 samples measured at different temperatures. [Figure 6]
[0017] The ionic conductivity and activation energy of various tested NaxLi3-xYCl6 samples are shown. [Modes for carrying out the invention]
[0011] Introduction
[0018] The three main functional components of a lithium-ion battery are the positive electrode, negative electrode, and electrolyte. The "negative electrode" often contains lithium metal with a layer of graphite inserted, and the "positive electrode" often contains lithium metal oxide with a layer of metal oxide inserted. The electrochemical roles of the electrodes are reversed between the anode and cathode depending on the direction of the current flowing through the cell. Often, the designations of anode and cathode are made in reference to their functions during discharge. Therefore, unless otherwise specified, the terms anode and cathode refer to the designations corresponding to discharge.
[0012]
[0019] During discharge, the lithium metal at the anode is oxidized in an oxidation half-reaction, generating lithium ions and electrons. While the electrons pass through the circuit, the generated lithium ions pass through the electrolyte towards the cathode. At the cathode, the lithium ions that have passed through the electrolyte combine with the metal oxide in a reduction half-reaction, where the metal species of the metal oxide is reduced by the electrons received at the cathode, to form lithium metal oxide.
[0013]
[0020] The designations of "anode" and "cathode" are technically reversed during battery recharging. During recharging, the metallic species of lithium metal oxide are oxidized to the metal oxide at the "anode," releasing lithium ions that migrate through the electrolyte to the "cathode," where they are reduced to lithium metal.
[0014]
[0021] Unlike conventional lithium-ion batteries which use liquid or gel electrolytes, solid-state batteries contain a solid electrolyte. Solid-state lithium-ion batteries can potentially offer improvements over conventional liquid-electrolyte lithium-ion batteries, including better safety, thermal stability, energy density, power density, and / or a wider operating temperature range. However, determining an effective solid electrolyte material is one of the challenges in developing effective solid-state lithium-ion batteries.
[0015]
[0022] The compounds disclosed herein are: Na x Li 3-x YCl6 (In the formula, x is greater than 0 and less than 3; for example, x is greater than 0.5 and less than 2.5.) For example, Na z LiYCl6, NaLi2YCl6, Na 0.5 Li 2.5 YCl6, Na 1.5 Li 1.5 YCl6 and Na 2.5 Li 0.5 YCl6 is an example. The disclosed compounds can be used as effective solid-state battery electrolytes. The disclosed compounds are [Equation] or [Equation] such as those having a space group, may have a trigonal crystal structure. The disclosed compounds may exhibit advantageous properties for solid-state battery electrolyte applications. Such properties include, for example, effective ionic conductivity (including room-temperature conductivity), formability / ductility, oxidation / reduction stability, and compatibility with anode and cathode materials.
[0016]
[0023] A trigonal crystal structure refers to a crystal structure falling within the scope of the trigonal crystal system (of the seven possible crystal systems), and thus exhibits three-fold symmetry around the central axis.
[0017]
[0024] Also disclosed herein is a solid electrolyte comprising the compound Na x Li 3-x YCl₆ (0<x<3). When used in a solid electrolyte, the disclosed compounds may have a trigonal crystal structure. Also disclosed herein is a solid-state battery comprising a solid electrolyte comprising the compound Na x Li 3-x YCl₆ (0<x<3). The solid electrolyte may advantageously function to conduct lithium ions and sodium ions. Accordingly, the solid-state battery may be configured as a lithium-ion battery or alternatively a sodium-ion battery.
[0018]
[0025] Also disclosed herein is a method of manufacturing a solid-state battery, such as a solid-state lithium-ion battery or a solid-state sodium-ion battery. The method comprises disposing a positive electrode in a container, disposing a negative electrode in the container, and disposing a solid electrolyte in the container between and in contact with the positive electrode and the negative electrode, wherein the solid electrolyte comprises Na x Li 3-x YCl₆ (0<x<3). The Na x Li 3-x YCl₆ (0<x<3) compound optionally comprises a trigonal crystal structure.
[0019] solid-state battery
[0026] FIG. 1A is a schematic diagram of an exemplary solid-state lithium-ion battery 100 during discharge, and FIG. 1B is a schematic diagram of the exemplary solid-state lithium-ion battery 100 during charging.
[0020]
[0027] As shown in FIG. 1A, an oxidation half-reaction occurs at the negative electrode 102 to generate lithium ions and electrons. The generated lithium ions pass through the solid electrolyte 106 toward the positive electrode 104. At the positive electrode 104, the lithium ions combine with electrons in a reduction half-reaction to form a lithium metal oxide. The battery 100 may also include a separator 108, but in some embodiments, the separator 108 may be omitted because the electrolyte 106 is solid.
[0021]
[0028] During charging, the lithium metal oxide at the positive electrode 104 is oxidized to generate lithium ions and electrons. The generated lithium ions pass through the solid electrolyte 106 toward the negative electrode 102. At the negative electrode 102, the lithium ions combine with electrons in a reduction half-reaction to form lithium metal.
[0022]
[0029] As described above, the solid electrolyte 106 is optionally provided with a trigonal crystal structure and may comprise Na x Li 3-x YCl6(0<x<3). Na x Li 3-x YCl6(0<x<3) may exhibit advantageous properties for solid-state battery electrolyte applications. Such properties include, for example, effective ionic conductivity (including room temperature conductivity), formability / ductility, oxidation / reduction stability, and compatibility with anode and cathode materials.
[0023]
[0030] The materials used in the electrodes may include any suitable electrode material or combination thereof known in the art for use in solid-state lithium-ion batteries. Exemplary anode materials include lithium metal, Li-In alloys, lithium titanate (e.g., Li 4-7 Ti5O12 and the like), other metal oxides (for example, SnO2, TiO2), carbon materials (for example, graphite, carbon nanotubes, graphene), silicon, and combinations thereof. Exemplary cathode materials include various metal oxides (for example, LiCoO2, LiNiO2, LiMn2O4, LiNi x Mn y Co 1-x-y O2, namely lithium nickel manganese cobalt oxide (NMC), and LiN x Al y Co 1-x-y O2, namely lithium nickel cobalt aluminum oxide (NCA)), sulfur-based materials (for example, Li2S), phosphate-based materials (for example, LiFePO4), and combinations thereof.
[0024]
[0031] The solid electrolyte Na x Li 3-x YCl6 (0<x<3) can conduct lithium ions and sodium ions, and thus can be utilized as an effective solid electrolyte in solid-state lithium-ion batteries and / or solid-state sodium-ion batteries. Sodium-ion batteries typically do not provide the same energy density as lithium-ion batteries. However, sodium-ion batteries can be more sustainable and economical, especially for specific applications where the lower energy density can be adequately compensated by a larger battery size.
[0025]
[0032] FIG. 2A is a schematic diagram of an exemplary solid-state sodium-ion battery during discharge, and FIG. 2B is a schematic diagram of an exemplary solid-state sodium-ion battery during charge.
[0026]
[0033] As shown in FIG. 2A, an oxidation half-reaction occurs at the negative electrode 202 to generate sodium ions and electrons. The generated sodium ions pass through the solid electrolyte 206 toward the positive electrode 204. At the positive electrode 204, the sodium ions combine with electrons in a reduction half-reaction. The battery 200 may also include a separator 208, but in some embodiments, the separator 208 may be omitted because the electrolyte 206 is solid.
[0027]
[0034] During charging, the material in the positive electrode 204 is oxidized to generate sodium ions and electrons. The generated sodium ions pass through the solid electrolyte 206 and travel toward the negative electrode 204. At the negative electrode 202, the sodium ions combine with electrons in a reduction half-reaction.
[0028]
[0035] The solid electrolyte 206 may optionally be provided with a trigonal crystal structure and comprise Na x Li 3-x YCl6(0<x<3). Na x Li 3-x YCl6(0<x<3) can exhibit properties that are beneficial for solid-state battery electrolyte applications. Such properties include, for example, effective ionic conductivity (including room temperature conductivity), formability / ductility, oxidation / reduction stability, and good compatibility with anode and cathode materials.
[0029]
[0036] The materials used in the electrodes may include any suitable electrode material or combination thereof known in the art for use in solid-state sodium-ion batteries. Exemplary anode materials include sodium metal, sodium metal alloys (e.g., Na-K, Na-Pb), carbon materials (e.g., hard carbon, graphite, carbon nanotubes, graphene, carbon arsenide), tin-based materials, sulfides (e.g., MoS2, TiS2), sodium titanates (e.g., oxides such as Na2Ti3O7), and combinations thereof. Exemplary cathode materials include various metal oxides (e.g., NaCoO2, NaNiO2, NaMn2O4), sulfur-based materials (e.g., Na2S), phosphate-based materials (e.g., NaFePO4, Na2FeP2O7 or Na3V2(PO4)3), and combinations thereof.
[0030]
[0037] Batteries 100 and 200 may also include a container (not shown). The container may be any container suitable for the intended use of the solid-state battery. The container may include metals (e.g., stainless steel, aluminum) and / or polymer materials. The container functions as a physical housing or casing for holding the anode, cathode and electrolyte in the appropriate positions and for providing mechanical support, electrical insulation and / or heat insulation.
[0031]
[0038] The container may also include a current collector for collecting current from the anode and cathode and distributing it to an external circuit. The current collector may be made of a conductive material such as copper or aluminum. The container may further include various sealing and / or barrier materials to prevent the ingress of moisture or contaminants. The container may further include various insulating layers (e.g., made of ceramic and / or glass) for the electrical insulation of the internal components. The container may further include various components for managing the thermal load and preventing overheating, such as heat sink components, thermal interface materials and thermal insulation materials.
[0032]
[0039] The solid electrolyte of a solid-state battery may also contain one or more dopants. One or more dopants may be added to improve the ionic conductivity of the electrolyte, modify vacancies in the electrolyte, affect the crystal structure of the electrolyte, promote the structural stability of the electrolyte, promote the thermal stability of the electrolyte, and / or affect the grain boundaries in the electrolyte. Exemplary dopants include La, Ca, Ni, Co, Gd, Pr, Mg, Al, and Sr. One or more dopants directed to the Y site may be included additionally or alternatively. Examples of such dopants include Zr, Ti, Si, Ge, and / or Sn.
[0033] Compound Synthesis
[0040] Na x Li 3-xYCl₆(0<x<3) compounds can be synthesized using methods known in the art for synthesizing alkali metal and rare earth metal halides. That is, a person skilled in the art can readily adapt known synthetic methods for other alkali metal and rare earth metal halides to the compounds disclosed in the present specification.
[0034]
[0041] For example, reference may be made to the solid-phase synthesis reaction described by Ito et al. in "Kinetically Stabilized Cation Arrangement in Li₃YCl₆ Superionic Conductor during Solid-State Reaction" (Adv. Sci. 2021, 8, 210413), the wet chemistry method described by Wang et al. in "A universal wet-chemistry synthesis of solid-state halide electrolytes for all-solid-state lithium-metal batteries" (Science Advances 2021, vol.7, issue 37), the solid-state and mechanochemical synthesis methods described by Schlem et al. in "Insights into the Lithium Sub-structure of Superionic Conductors Li₃YCl₆ and Li₃YBr₆" (Chem. Mater. 2021, 33, 1, 327-37), and / or the synthesis described by Hu et al. in "Revealing the Pnma crystal structure and ion-transport mechanism of the Li₃YCl₆ solid electrolyte" (Cell Reports Physical Science 4, 101428).
[0035]
[0042] Generally, the synthesis of the disclosed compounds can be carried out by mixing stoichiometrically appropriate amounts of suitable precursor components (e.g., NaCl, LiCl, and YCl3). The precursor mixture can be subjected to mechanical processing such as ball milling and / or other suitable processing techniques (e.g., manual techniques such as attrition milling, jet milling, vibratory milling, hammer milling, roller milling, colloidal milling, cryogenic milling, ultrasonic milling, pin milling, and / or mortar and pestle grinding). Optionally, suitable volatile organic liquids such as acetone and / or alcohols can be added to the mixture to promote homogenization.
[0036]
[0043] Subsequently, the treated precursor mixture can be subjected to heat treatment to initiate and carry out a solid reaction. The heat treatment may be carried out in a suitable vessel formed from a material substantially chemically inert to the reactants at the heating temperature used. Exemplary materials include suitable metals such as precious metals. The treated precursor material may optionally be pelletized before heat treatment.
[0037]
[0044] The heat treatment can be carried out at a temperature and time sufficient to carry out the solid reaction. During the synthesis of Na2LiYCl6, it was found that a temperature of 627°C conveniently yielded a single-phase trigonal Na2LiYCl6, while a lower temperature of 277°C resulted in the presence of the LiCl phase. Therefore, the heat treatment temperature can be 300°C or higher, 400°C or higher, 500°C or higher, 600°C or higher, for example, up to 700°C, 800°C, 900°C or 1,000°C, or within a range having endpoints defined by any two of the aforementioned values.
[0038]
[0045] Following heat treatment, the material may undergo further mechanical treatment, such as one or more of the mechanical treatment techniques described above.
[0039]
[0046] The resulting product can be analyzed using analytical methods known in the art. Examples include X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), nuclear magnetic resonance (NMR) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, Raman spectroscopy, differential scanning calorimetry (DSC), X-ray photoelectron spectroscopy (XPS), and electron paramagnetic resonance (EPR).
[0040] Manufacture and Use of Batteries
[0047] A method of manufacturing a solid-state battery, such as a solid-state lithium-ion battery or a solid-state sodium-ion battery, may comprise disposing a positive electrode in a container, disposing a negative electrode in the container, and disposing a solid electrolyte in the container between and in conductive contact with the positive electrode and the negative electrode, wherein the solid electrolyte comprises Na x Li 3-x YCl6(0<x<3). The solid electrolyte optionally comprises a trigonal crystal structure.
[0041]
[0048] The container may be any container suitable for the intended use of the solid-state battery. The container functions as a physical housing or casing to hold the anode, cathode, and electrolyte in place, and provide mechanical support, electrical insulation, and / or thermal insulation. The container may include any of the components described elsewhere herein.
[0042]
[0049] The solid-state battery may be used in any application suitable for battery power. Examples include consumer electronic devices such as laptop computers, mobile phones, and tablets, wearable devices such as smart watches and other fitness tracking devices, implantable medical devices such as pacemakers and neurostimulators, electric vehicles (e.g., cars, motorcycles, scooters), unmanned aerial vehicles (UAVs) including drones, grid and / or renewable (e.g., solar, wind) surplus energy storage, power tools, as well as any other application where battery power is suitable.
Examples
[0043] Examples
[0050] Example 1 describes the synthesis process in which Na2LiYCl6 was produced, as well as detailed characteristic evaluation and conductivity tests. Examples 2 to 5 relate to Na when used as a solid-state battery electrolyte x Li 3-x YCl6 (0<x<3) are prophetic examples intended to demonstrate the expected properties and advantages. The prophetic results described below are reasonably foreseeable based on the content of the present disclosure.
[0044] Example 1 - Na x Li 3-x Synthesis and characteristic evaluation of YCl6
[0051] Synthesis procedure: All fabrication processes were carried out in an Ar-filled glove box (VAC) (<0.5 ppm O2, 0.5 ppm moisture). Stoichiometric amounts of precursors NaCl (Sigma Aldrich, ≧99%), LiCl (Sigma Aldrich, ≧99%) and YCl3 (Sigma Aldrich, 99.99%) were manually mixed in an agate mortar for 30 minutes. 1 gram of the mixture was pressed into pellets with a diameter of 12 mm under a pressure of 200 bar using a hydraulic press. The pellets were then loaded into quartz ampoules under vacuum and flame-sealed. The sealed ampoule containing the pellets was heated to a temperature of 450°C to 550°C at a ramp rate of 10°C / min according to the stoichiometry of the sample using a tube furnace, and held at this temperature for 5 hours. The sample was then allowed to cool naturally. After cooling, the sample ampoule was carefully opened in the glove box, finely crushed with a mortar and pestle, and then subjected to characteristic evaluation. All products remained in the glove box during processing.
[0045]
[0052] XRD Characterization: Powder XRD measurements were performed using a Rigaku SmartLab SE Bragg-Brentano diffractometer equipped with a Cu source (λ=1.5418 Å) and a D / teX Ultra 250 ID high-speed position-sensing detector. The sample was placed in an SiO2 zero background well holder and then covered with a single layer of Kapton tape inside a glove box to avoid moisture degradation. The diffraction pattern of the synthesized Na2LiYCl6 is shown in Figure 3.
number
number
number
[0046]
[0053] Elemental analysis: Using XPS, Na x Li 3-x The atomic percentages of Li, Na, Y, and Cl in the YCl6 sample were confirmed. For x from 0 to 3, the Li / Na ratio was qualitatively consistent with the nominal value from the composition. For XPS, Na x Li 3-xYCl6 (100 mg) fine powder was compressed into pellets via a hydraulic press (100 bar) in a stainless steel pressure die inside an Ar-filled glove box. The pellets were then loaded onto a sample holder and moved to an XPS analysis chamber without exposure to air. XPS analysis was performed using a Kratos Axis Ultra DLD spectrometer consisting of an Al Kα monochromatic X-ray source (1486.6 eV) and a high-resolution spherical mirror analyzer. The X-ray source was operated at 150 W output, and the emitted photoelectrons were collected through an analyzer entrance slit perpendicular to the sample surface. High-resolution spectra were acquired at a pass energy of 40 eV with a step size of 0.1 eV. The XPS spectra were calibrated using a C1s signal at 285 eV. Data were processed using CasaXPS software. The composition of the sample was calculated using the Li 1s, Na 2s, Y 3d, and Cl 2p high-resolution spectra. Figure 4 shows the atomic percentages of Na, Li, Y, and Cl from the XPS analysis.
[0047]
[0054] The relative elemental ratios of Na, Y, and Cl in the bulk sample were confirmed by SEM and energy-dispersive X-ray spectroscopy (EDS). Since Li is a light element, it cannot be detected by EDS. Therefore, only the relative ratios of non-Li elements are determined through this technique. The sample powder was pressed into a flat, thin pellet and placed on conductive double-sided carbon adhesive dots positioned on an aluminum stub. An electron beam with a current of 1.6 nA and an accelerating voltage of 20 kV was used at a working distance of 10 mm. Different compositions (Na x Li 3-x At least 10 different sites on each pellet of YCl6 (x=0, 0.5, 1, 1.5, 2.3) were measured for the average statistics of elemental quantification.
[0048]
[0055] Characterization of ionic conductivity: 110 mg of electrolyte fine powder was loaded into a 12 mm diameter Split Cell (MSE Supplies) and sandwiched between two stainless steel electrodes. The cell was then cold-pressed to 100 bar using a hydraulic press inside an Ar-filled glove box. The cell was then removed from the glove box, loaded into a pressure jig, and pressurized to 250 MPa. Impedance measurements were performed using a Biologic VMP3 at an applied AC potential of 100 mV over a frequency range of 1 MHz to 100 mHz. EIS was collected at various temperatures from 100°C to 25°C. At each temperature, the cell was allowed to stand for 2 hours before EIS spectrum acquisition. The thickness of each pellet was measured using a digital micrometer (Mitutoyo) after the completion of impedance measurements. The ionic conductivity of the pelletized electrolyte was determined using the EIS data.
[0049]
[0056] Na measured at different temperatures x Li 3-x The ionic conductivity of YCl6 is shown in Figure 5. When Li is introduced instead of Na, the conductivity at 100°C is slightly lower than that observed in the parent Na3YCl6 material, at 6.0 × 10⁻⁶. -8 Compared to S / cm, specifically at a substitution level of 1 / 3, the ionic conductivity increased by more than two orders of magnitude, which is 2.2 × 10⁻⁶ at 100°C. -6 This is illustrated by Na2LiYCl6 (x=2), which exhibits a conductivity of S / cm. The measured ionic conductivity across varying x values consistently shows an increasing trend associated with the increase in the Li component. This trend suggests that the increased mobility of Li+ ions actively contributes to the measured conductivity in these substituted compositions.
[0050]
[0057] As shown in Figure 6, a significant reduction in activation energy was also observed with the introduction of lithium (x=0.5~3) compared to the parent Na3YCl6 (0.82eV). In particular, Na2LiYCl6 (similar to the parent Na3YCl6)
number
[0051]
[0058] This enhancement of conductivity and reduction of activation energy are likely attributable to the involvement of Li+ ions in ion transport and potential structural changes in the crystal structure, such as the expansion of ion diffusion channels and local structural disorder resulting from Li+ substitution. The trigonal crystal structure of parent Na3YCl6 contains one fully occupied Na site and two partially occupied Na sites, enabling diffusion pathways through and between channels and predominantly promoting ion conduction along the c axis
[38] . The increased conductivity observed upon lithium substitution suggests that the changing occupation and distribution of Na and Li sites modulate the energy landscape, possibly along the c axis, thereby promoting accelerated ion diffusion.
[0052] Example 2 - Stability Analysis
[0059] Stability testing of Na2LiYCl6 is performed in one or more environments that demonstrate material stability in the presence of oxygen and water vapor, using differential scanning calorimetry (DSC) or similar techniques that characterize materials in an inert environment. The Na2LiYCl6 material is expected to exhibit effective stability in such environments, together with other parts of the battery (anode and cathode), at least equivalent to known solid electrolyte materials.
[0053] Example 3 - Additional conductivity analysis
[0060] Conductivity analysis of Na2LiYCl6 was performed, including variable-temperature AC impedance analysis with a 2 / 3 electrode setup to identify bulk / grain boundary contributions, variable-temperature DC resistance analysis to obtain transport fractions, and solid-state nuclear magnetic resonance (NMR) spectroscopy of selected samples to obtain ion diffusion constants. Na2LiYCl6 is expected to exhibit effective lithium and sodium conductivity.
[0054] Example 4 - Electrochemical properties
[0061] The electrochemical properties were characterized, including electrochemical impedance spectroscopy and conductivity fitting over a temperature range, testing of the material in coin cells with lithium metal or graphite anodes and NMC cathodes (up to 100 cycles), and post-analysis using infrared (IR), XPS, and Raman spectroscopy of the coin cells to assess electrochemical stability and failure mode prediction. The Na2LiYCl6 electrolyte material is expected to exhibit effective electrochemical properties.
[0055] Example 5 - Interface Test
[0062] The test half-cell is formed by bonding a Na2LiYCl6 electrolyte to a lithium metal anode to determine the stability of the electrode-electrolyte interface. The Na2LiYCl6 electrolyte is expected to form and maintain an effective interface at least equivalent to that of known solid electrolyte materials.
[0056] Additional terms and definitions
[0063] All publications described herein (including patents, patent applications, and academic papers) are incorporated herein by reference.
[0057]
[0064] The embodiments disclosed herein should be understood to include / inclusive of the disclosed components and, therefore, may include additional components not specifically described. Optionally, the embodiments disclosed herein may essentially or completely exclude components not specifically described. That is, components not disclosed may, at their discretion, be completely or essentially excluded from the embodiments disclosed herein.
[0058]
[0065] For example, Na x Li 3-xA solid battery comprising a solid electrolyte containing YCl₆ (0<x<3) may essentially exclude or completely exclude other electrolyte compounds not specifically disclosed herein, including any electrolyte having a different compound formula and / or any electrolyte having a different crystal structure (e.g., any electrolyte having a non-trigonal crystal structure). Similarly, the disclosed solid electrolytes may essentially exclude or completely exclude one or more elements not specifically disclosed as being part of the electrolyte compound. For example, the disclosed solid electrolytes may essentially exclude or completely exclude one or more of Be, Sc, Cs, Rb, Zr, Ti, Hf, Ta, Ca, Sr, Mg, or Fe.
[0059]
[0066] An embodiment that "essentially excludes" a certain component may include trace amounts and / or non-functional amounts of that component. For example, an "essentially excluded" component may be present in an amount of 1% or less, 0.5% or less, 0.1% or less, or 0.01% or less by total weight of the composition. This is equally applicable to other negative modifiers, such as similar phrases using other synonyms of "essentially free of", "essentially not containing", "substantially" or "inherently".
[0060]
[0067] A composition that "completely excludes" a certain component contains no detectable amount of that component (i.e., no amount exceeding any inherent background signal associated with a suitable test instrument) when analyzed using standard compositional analysis techniques such as, for example, microscopy imaging techniques, chromatography techniques (e.g., thin-layer chromatography (TLC), gas chromatography (GC), liquid chromatography (LC)), or spectroscopy techniques (e.g., Fourier-transform infrared (FTIR) spectroscopy).
[0061]
[0068] In addition, unless otherwise indicated, any numbers representing quantities, constituents, distances, or other measurements used herein and in the claims should be understood to be optionally modified by the term “about.” When terms such as “about,” “approximately,” or “substantially” are used in relation to a stated quantity, value, or condition, they may be interpreted as meaning a quantity, value, or condition that deviates by less than 20%, less than 10%, less than 5%, less than 1%, less than 0.1%, or less than 0.01% from the stated quantity, value, or condition.
[0062]
[0069] Any headings and subheadings used herein are for structural purposes only and are not intended to limit the scope of this specification or the claims.
[0063]
[0070] It should also be noted that, as used herein and in the appended claims, the singular forms “a,” “an,” and “it” do not exclude multiple references unless the context clearly indicates otherwise. Thus, for example, embodiments referring to a single reference may also include two or more such references.
[0064]
[0071] The embodiments described herein may also include characteristics and / or features (e.g., components, elements, members, parts, and / or components) described in one or more distinct embodiments, and are not necessarily strictly limited to the features explicitly described for that particular embodiment. Accordingly, various features of a given embodiment may be combined with and / or incorporated into other embodiments of the Disclosure. Accordingly, the disclosure of specific features relating to a particular embodiment of the Disclosure should not be interpreted as limiting the application or inclusion of such features to that particular embodiment. Rather, it is understood that other embodiments may also include such features.
Claims
1. Anode (102), Cathode (104) and, A solid electrolyte (106) is positioned between the anode (102) and the cathode (104) and in conductive contact with them, A solid battery (100) including, The solid electrolyte (106) is Na x Li 3-x YC- 6 (In the formula, x is greater than 0 and less than 3.) A solid battery (100) including the above.
2. The Na x Li 3-x YCl 6 The solid battery (100) according to claim 1, comprising a trigonal crystal structure.
3. The solid battery according to claim 1, wherein the solid lithium-ion battery (100).
4. The solid-state battery according to claim 3, wherein the anode (102) comprises one or more of lithium metal, Li-In alloy, lithium metal oxide, carbon material, or silicon.
5. The solid battery (100) according to claim 4, wherein the lithium metal oxide comprises one or more of lithium titanate, tin oxide, or titanium oxide.
6. The solid-state battery (100) according to claim 4, wherein the carbon material comprises one or more of graphite, carbon nanotubes, or graphene.
7. The solid-state battery (100) according to claim 3, wherein the cathode (104) comprises one or more of a metal oxide, a sulfur-based material, or a phosphate-based material.
8. The solid battery (100) according to claim 7, wherein the metal oxide comprises one or more of cobalt oxide, nickel oxide, manganese oxide, nickel-manganese-cobalt oxide, or nickel-cobalt-aluminum oxide.
9. The solid battery according to claim 1, wherein the solid sodium ion battery (200).
10. The solid-state battery according to claim 9, wherein the anode (202) comprises one or more of sodium metal, sodium metal alloy, carbon material, tin-based material, sulfide, or sodium titanate.
11. The solid battery (200) according to claim 10, wherein the sodium metal alloy comprises one or more Na-K or Na-Pb.
12. The solid battery (200) according to claim 10, wherein the carbon material comprises one or more of hard carbon, graphite, carbon nanotubes, graphene, or arsenide.
13. The solid-state battery according to claim 9, wherein the cathode (204) comprises one or more of a metal oxide, a sulfur-based material, or a phosphate-based material.
14. The solid battery (200) according to claim 13, wherein the metal oxide comprises one or more of cobalt oxide, nickel oxide, manganese oxide, nickel-manganese-cobalt oxide, or nickel-cobalt-aluminum oxide.
15. A solid-state battery (100) according to claim 1, configured for powering consumer electronic devices, wearable devices, implantable medical devices, electric vehicles, unmanned aerial vehicles (UAVs), power tools, or for grid and / or surplus renewable energy storage.
16. The solid electrolyte contains Na 2 LiYCl 6 , NaLi 2 YCl 6 , Na 0.5 Li 2.5 YCl 6 , Na 1.5 Li 1.5 YCl 6 or Na 2.5 Li 0.5 YCl 6 The solid-state battery (100) according to claim 1, comprising one or more of the foregoing.
17. A method for manufacturing a solid battery (100), The positive electrode (104) is placed inside the container, The negative electrode (102) is placed inside the container, The solid electrolyte (106) is placed between the positive electrode (104) and the negative electrode (102) within the container and in conductive contact with them, Includes, The solid electrolyte (106) is Na x Li 3-x YC- 6 (In the formula, x is greater than 0 and less than 3.) Methods that include...
18. The Na x Li 3-x YCl 6 The method according to claim 17, wherein the crystal structure is trigonal.
19. The method according to claim 17, wherein the solid battery is configured as a lithium-ion battery (100).
20. The method according to claim 17, wherein the solid battery is configured as a sodium-ion battery (200).